Studying the factors behind breaching a psychological contract between employee and employer: A cross-country analysis - Fyodorova A.E. (Ural State University of Economics, 2019)
The growing instability in labour markets, restructuring and downsizing workforce, precariatization and staff flexibilization underlie the increasing importance of a psychological contract and employees’ confidence in their employer in modern labour relations. The study aims to explore the role of trust and psychological contract in HR management at an enterprise. The methodological basis includes psychological contract theory and the concept of transition contract. Using the results of an annual sociological survey performed in five countries with different models of economic development (Russia, Сzech, Latvia, Pakistan and Italy), the authors try to identify the similarities and differences of these countries regarding the way in which the existing conditions of employee-employer relationships influence the fulfilment of explicit and latent aspects of a psychological contract. We identify the major reasons behind mismatches between employees’ and employers’ expectations that cause mistrust, uncertainty and erosion of labour relations. Empirical data obtained in 2015–2017 during the survey of employees in various economic sectors allow us to draw a conclusion about the multiplicity of forms of a psychological contract breach, to conduct a comparative analysis of the trends prevailing in the countries under consideration, as well as to identify their similar and distinctive features. The authors are certain that managers should understand the significance of trust and a psychological contract in HR management and take it into consideration when developing a human resource management strategy.